Bahasa Inggris - Fitra, Muh. Al Fachrizah; Dollah, Syarifuddin; Baa, Sultan (AL MA'ARIEF : Jurnal Pendidikan Sosial dan Budaya, 2024)
This research explores the phenomenon of culture shock experienced by the Minangkabau community in Makassar, focusing on its stages and effects. The research employs a qualitative ethnographic design, gathering data through interviews, observations, and documentation to understand the cultural adaptation process. Guided by Kalervo Oberg's U-Curve theory of adjustment, the findings reveal that Minangkabau migrants undergo four distinct stages of culture shock: honeymoon, frustration, adjustment, and adaptation/acceptance. In the honeymoon phase, migrants experience excitement and fascination as they engage with Makassarese culture. However, this enthusiasm fades in the frustration phase, where language barriers, communication differences, and unfamiliar social norms create stress and isolation. The adjustment phase marks a turning point, as migrants develop coping strategies, learn local customs, and build social networks. Finally, the adaptation and acceptance phase sees them achieving a balance between preserving their cultural identity and integrating into the host society. The research concludes that while culture shock presents initial challenges, it ultimately fosters personal growth, resilience, and cultural competence. The findings underscore the importance of social support, cultural awareness, and adaptability in facilitating successful cultural transitions. This research highlights how culture shock, despite its difficulties, can lead to positive outcomes, enriching both the migrants' lives and the multicultural landscape of Makassar.